Kemampuan Analisis Artikel Ilmiah Mahasiswa PGMI IAIN Sorong - Oki Sandra Agnesa; Dita Purwinda Anggrella (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The ability to analyze scientific articles is important for students to have to complete their studies. This study aimed to describe the ability to analyze scientific articles of fifth-semester students of PGMI IAIN Sorong, which was measured based on the ability to recognize the rhetorical move of articles. The research design was in the form of a survey with a sample of 28 students. The study results, which were analyzed using the percentage technique, showed that the analytical ability of the fifth-semester students of PGMI IAIN Sorong was still low in identifying the rhetorical movement of articles. The objective aspect (85.71% correct answer) and conclusion (75% correct answer) are the easiest aspects to identify, followed by the implication aspect (53.57% correct answer), while the motive, support, counterargument, and refutation aspects (0% correct answer)  could not be identified.